Tenacity Of German Conspiracy Against Nazi Regime In Brian Singer's Valkyrie Movie (2008): A Sociological Approach - Adiantika, Hanif Nurcholish (2012)
The major problem in this study is how tenacity is reflected in Brian Singer's Valkyrie movie by using a Sociological Approach. It is conducted by analyzing the movie based on its structural elements and based on Sociological analysis. This research is qualitative research. Types of data of the study are text and image taken from two data sources: primary and secondary. The primary data source is Valkyrie movie directed by Brian Singer released in 2008. While the secondary data sources are other materials taken from books, internet and other relevant information. Both data are collected through library research and analyzed by descriptive analysis. Using a sociological analysis as the theoretical framework, the research shows the following findings. First, based on structural analysis of this movie, it is evident that in this movie, Brian Singer as the director conveys the tenacity of German conspiracy to assassinate Adolf Hitler in order to end the World War II. Second, based on sociological analysis, it is apparent that in this movie, Brian Singer illustrates how a sociological phenomenon related to tenacity of the human being in order to save a country from total destruction in the middle of the horrible war.